Da'wa Critical Discourse Analysis in the Omar and Hana Cartoon Film on Alalala Raju Episode - Silvia Putri Utami; Yudi Asmara Harianto (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2021)
Cartoons, which are closely associated with children, tend to contain violence and mere entertainment. It is still rare to find comics that have Islamic values. This study aims to critically analyse the construction of Islamic values in the cartoon film Omar and Hana episode Alalala Raju. The research was qualitative research using the Van Dijk model of critical discourse analysis and content analysis of the da'wa message. The data was from a YouTube channel called Omar & Hana - Islamic Children's Songs. The study results found that the structure of the film's text contains a discourse of advice to children to share objects they have and love. The social cognition system explains that this film has a vision and mission to instil Islamic values and joy in children worldwide, namely by sharing. And the social context that becomes the background is the concern of parents about the lack of Islamic cartoons and the difficulty of children sharing. The meaning of discourse contained in the film is as a message of da'wa morals.